Mathematics in STEM in the context of conservation: Exploration in mathematics learning - Marlina, Atin; Fauziyyah, Iis Nita (Interdisciplinary International Journal of Conservation and Culture, 2024)
This study systematically reviewed the literature linking mathematics learning to STEM education in the context of conservation. An in-depth analysis of 200 scientific articles revealed a significant correlation between STEM and conservation efforts. However, research specifically exploring the central role of mathematics in conservation-based learning was relatively limited. The study successfully identified several best practices, such as using mathematical modeling to analyze complex environmental phenomena and developing problem-based projects that integrate multiple STEM disciplines. However, there was a significant knowledge gap regarding optimal learning design, selection of relevant conservation topics, and comprehensive evaluation of the impact of this learning on students’ conceptual understanding and behavioral changes. To fill this gap, further research was needed to develop a more comprehensive framework integrating mathematics into conservation-based STEM learning. This framework was expected to guide educators in designing effective and meaningful learning experiences and allow for more systematic evaluation of learning outcomes. In addition, future research should also explore the role of digital technologies in supporting conservation-based mathematics learning, as well as the challenges and opportunities faced in implementing this approach across cultural and social contexts.